2019
DOI: 10.3390/su11184994
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing-Based Analysis of Landscape Pattern Evolution in Industrial Rural Areas: A Case of Southern Jiangsu, China

Abstract: With the rapid economic development of industrial rural areas in Southern Jiangsu, the rural landscape and ecological environment of these industrial rural areas are getting damaged. Based on GIS and RS techniques, Landsat Satellite remote sensing images from 1981, 1991, 2001, 2011 and 2018 were collected for Jiangyin, Zhangjiagang, Changshu and Kunshan, to extract landscape pattern indexes and spatial distribution data. Landscape pattern indexes of the patch-class level and landscape level from each year were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The present study confirmed that the settlement area, the shape index, and the spreading index had a more significant coupling relationship with the degree of the landscape fragmentation in woodlands and biological reserves, which was consistent with the findings of Zhu et al [92] and Xu et al [93]. However, the existing studies did not analyze the specific manifestations of the differences in the effects of settlement indicators on woodlands and biological reserves.…”
Section: Settlement Patterns and Fragmentation Of Woodlands And Biolo...supporting
confidence: 92%
“…The present study confirmed that the settlement area, the shape index, and the spreading index had a more significant coupling relationship with the degree of the landscape fragmentation in woodlands and biological reserves, which was consistent with the findings of Zhu et al [92] and Xu et al [93]. However, the existing studies did not analyze the specific manifestations of the differences in the effects of settlement indicators on woodlands and biological reserves.…”
Section: Settlement Patterns and Fragmentation Of Woodlands And Biolo...supporting
confidence: 92%
“…This land cover is somewhat sensitive to erosion [20], very slow permeability and compaction of topsoil [33] with the characteristics of soil types that have low fill weights [34], classification of humid rainfall intensity, and mountainous topography that is prone to failure surface slopes [35]. The evolution of landscape patterns leads to changes in spatial structure and landscape ecosystems which will ultimately affect ecological security [36]. Forests, plantation, and water bodies are the main source of ecological security [37], external forces (eg typhoons with heavy rainfall and earthquakes), and human activities (eg changes in land cover and deforestation result in complex interactions of various landslides [38].…”
Section: Resultsmentioning
confidence: 99%
“…When the landscape has only one patch, the SHDI equals 0, and when the patch type increases, the value of the SHDI also increases. The evolution process of landscape patterns can be determined by investigating the basic characteristics, morphological changes and spatiotemporal evolution of the various landscape categories [38]. Table 3.…”
Section: Landscape Indexesmentioning
confidence: 99%